Morphological and Histopathologic Study of the Cow Skin in the Early Stage After a Tick Bite in Najaf Al-Ashraf - Algam, Baidaa Ghanem (Medical Science Journal for Advance Research, 2026)
Total of number of hard ticks was 80 samples were collected from cattle in province of Najaf. They were diagnosed phenotypically in the laboratories . ticks were recorded: Hyalomma with three species belonging to Hyalomma: H. anatolicum, H. truncatum, H. excavatum .Ticks are comparatively big acarines, which are vertebrate ectoparasites that feed on blood.Crusts and scabs were often the most common gross pathologic lesions, and they primarily resulted from traumatization or degeneration following previous primary lesions.In the current investigation, some clinical symptoms like overall weakness, skin redness, and the observation of some scratches in the tick attachment sites were observed during the visual inspection of infested animals. Both sides of the epidermis are inflammatory and more, particularly the lymphocytes, mononuclear cells, and eosinophil cells.